1987
DOI: 10.1177/109019818701400305
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Structured Education Program on Knowledge and Psychomotor Skills of Patients Using Beclomethasone Dipropionate Aerosol for Steroid Dependent Asthma

Abstract: The purpose of the study was to evaluate the efficacy of a structured education program on knowledge and psychomotor skills of subjects using inhaled beclomethasone dipropionate. The sample was comprised of 26 male outpatients with a mean age of sixty years (range 49-69 yrs) and mean educational level of 11 years (range 7-18 yrs). Subjects were tested to assess knowledge of drug action, self-administration, and side effects. Skill in self-administration was assessed by two independent raters who were blind to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…The control group (group 4) which was not exposed to any asthma education resources, showed modest but statistically significant improvements in asthma-related knowledge. Other researchers noted similar effects, concluding that increases in baseline knowledge assessments may stimulate both experimental and control group participants to consider and seek further information about text content (Heringa et al 1987).…”
Section: Discussionmentioning
confidence: 82%
“…The control group (group 4) which was not exposed to any asthma education resources, showed modest but statistically significant improvements in asthma-related knowledge. Other researchers noted similar effects, concluding that increases in baseline knowledge assessments may stimulate both experimental and control group participants to consider and seek further information about text content (Heringa et al 1987).…”
Section: Discussionmentioning
confidence: 82%
“…Observation of patient teaching was intended but not carried out, due to time constraints. Other studies have either used only one instructor (Heringa et al, 1987) or fail to give details as to how uniformity of teaching was achieved (O'Bey et al, 1982).…”
Section: Inhalation Techniquementioning
confidence: 99%
“…Several studies have focused on the effects of educational programmes on people's ability to use inhalers. Heringa et al (1987) considered both knowledge and psychomotor skill of patients and concluded that a structured education programme is an effective method for improving skill of inhaler use; the study did not focus specifically on elderly people. Similar conclusions were drawn from an earlier study by O'Bey et al (1982).…”
mentioning
confidence: 99%
“…During the past decade, understanding of asthma self-management has developed greatly, and there is a general agreement that more effective methods of educating patients are needed to reduce morbidity and mortality from the disease (9)(10)(11)(12). Asthma selfmanagement education programs share three basic premises: the physician and patient are partners in the management of asthma; the context for management is variable, with the patient, his or her situation, medical treatment, and the home environment continually changing; and management tasks performed at home must fit the family's lifestyle (13).…”
mentioning
confidence: 99%